The Relationship Between Digital Payment Adoption and Revenue Growth in Online Retail Companies - Irmayanti, Irmayanti (LP2M IBK Nitro, 2025)
Digital payments are transforming how retail companies conduct business, offering faster transactions, greater convenience, and improved customer satisfaction. While many studies have examined adoption trends and consumer behavior, little is known about the financial impact of digital payment adoption, especially in emerging markets. This study explores the relationship between digital payment adoption and revenue growth in Indonesian online retail companies. Using data from 42 firms between 2019 and 2023, the study applies panel regression analysis to test whether digital payment adoption contributes to revenue performance. The results show that higher levels of digital payment adoption are strongly associated with increased revenue growth. Larger firms also benefit more from adoption, while firm age and product type have no significant effect. These findings highlight that digital payments are not only a technological convenience but also a strategic driver of financial growth in Indonesia’s online retail sector.